2021
DOI: 10.1038/s41598-021-00655-2
|View full text |Cite
|
Sign up to set email alerts
|

A fan-attached jacket worn in an environment exceeding body temperature suppresses an increase in core temperature

Abstract: We examined whether blowing hot air above body temperature under work clothing may suppress core temperature. Nine Japanese men engaged in two 30-min bicycle ergometer sessions at a workload of 40% VO2max at 40 °C and 50% relative humidity. The experiment was conducted without wearing any cooling apparatus (CON), wearing a cooling vest that circulated 10.0 °C water (VEST), and wearing a fan-attached jacket that transferred ambient air underneath the jacket at a rate of 30 L/s (FAN). The VEST and FAN conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…9 Hashimoto et al compared the cooling effect of ambient air-ventilated vest and water-cooled jacket supplied with chilled water at 10°C worn by nine subjects during moderate exercise in a hot and dry environment (40°C, 50% RH) and found both devices effectively reduced the elevation of core temperature. 10 Ciuha U compared the efficacy of air-cooled vest and water-cooled vest using thermal manikin in a hot environment (35°C, 35% RH), and found the water-cooled vest had higher cooling power than the aircooled vest at least until the coolant ice melted. 11 Barwood et al found that whole-body fanning was the most effective and a liquid-cooled garment was the least effective compared with hand immersion, an air-cooled garment, and a phase change garment in post-exercise cooling in a 31°C environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Hashimoto et al compared the cooling effect of ambient air-ventilated vest and water-cooled jacket supplied with chilled water at 10°C worn by nine subjects during moderate exercise in a hot and dry environment (40°C, 50% RH) and found both devices effectively reduced the elevation of core temperature. 10 Ciuha U compared the efficacy of air-cooled vest and water-cooled vest using thermal manikin in a hot environment (35°C, 35% RH), and found the water-cooled vest had higher cooling power than the aircooled vest at least until the coolant ice melted. 11 Barwood et al found that whole-body fanning was the most effective and a liquid-cooled garment was the least effective compared with hand immersion, an air-cooled garment, and a phase change garment in post-exercise cooling in a 31°C environment.…”
Section: Introductionmentioning
confidence: 99%
“…Troy et al evaluated the cooling effects of ambient air‐ventilated vest during moderate exercise in a hot and dry environment (40°C, 20% RH) and found the system reduced physiological strain 9 . Hashimoto et al compared the cooling effect of ambient air‐ventilated vest and water‐cooled jacket supplied with chilled water at 10°C worn by nine subjects during moderate exercise in a hot and dry environment (40°C, 50% RH) and found both devices effectively reduced the elevation of core temperature 10 . Ciuha U compared the efficacy of air‐cooled vest and water‐cooled vest using thermal manikin in a hot environment (35°C, 35% RH), and found the water‐cooled vest had higher cooling power than the air‐cooled vest at least until the coolant ice melted 11 .…”
Section: Introductionmentioning
confidence: 99%
“…When recreational athletes have limited to access to ample amounts of water and ice, or there is a lack of electricity to maintain water temperature, cooling may be considered using a different method. Recently, a fan-cooling jacket was recently developed to mitigate the thermal strain and the risk of heat stroke during activity in hot outdoor environments ( 13 , 14 ). This jacket can be cooled via the process of circulating airflow underneath clothing by two small fans attached to the back of the waist and can be easily applied to recreational athletes.…”
Section: Introductionmentioning
confidence: 99%
“…In the industrial working environment, garments equipped with cooling materials, such as ice, phase change materials, and cooled water-perfusion systems, have been developed [ 7 9 ]. Also, a long-sleeve jacket that is similar to work clothing but has small fans attached to the back of the waist has sometimes been used among workers [ 10 12 ]. Internal cooling involves the introduction of a cold medium to the body through the mouth (and/or nose, in the case of breathing), and includes the consumption of cold fluids or ice and inhalation of cold air [ 6 ].…”
Section: Introductionmentioning
confidence: 99%